Studi Kinerja Rancang Bangun Sistem Penampil Informasi Hybrid Pada Perahu Nelayan Berbasis Google Maps - Nugraha, Sapta; Kurniawan, Hendra (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
Boat is a type of traditional public transportation of the Indonesian people, especially the people in Penyengat Island, Riau Islands Province. Communities on Penyengat Island have many traditional boats that do not have a Global Maritime Distress and Safety System (GMDSS) for shipping standards. Shipping standards are needed so that the safety factor in sailing is more awake. Sailing safety factors are needed in getting help if an accident on a fishing boat occurs. Delay in help due to ignorance of the information about the accident and the position of the ship that is difficult to detect. Based on the description, it will be appointed a performance study on the design of a hybrid information display system on fishing boats to determine the location of the accident that will be displayed in the form of Google Maps. Google Maps is a digital map service application developed by Google. The combination of Google Maps and the Global Positioning System (GPS) receiving device is a very useful combination. In addition, the hybrid system used is a combination of manual systems in the form of buttons and automatic systems in the form of tilt sensors on the boat. Research results obtained that users can find out the position of objects based on latitude and longitude coordinates displayed using Google Maps.